Colton's secret weapon - Quinn, Tara Taylor (Coltons of Alaska, 2025)
They're world apart...until danger draws them together. Mitchell Colton doesn't want Dove St. James as a client. Her free-spirited style couldn't be more different from his just-the-facts approach. Now, though, she needs a lawyer-and he can't quite bring himself to tell her no. The seemingly simple case takes a disturbing turn when an intruder destroys Dove's yoga studio and her father goes missing. Before he even realizes what he's doing, Mitchell insists that she move in with him until the threats against her stop. But keeping her safe may be harder than resisting the pull that neither of them can deny...